Analysis of the Effect of Cut Sweep Ratio of Lily Impeller on the Distribution of Dissolved Oxygen - Mohammad Tauviqirrahman; Eflita Yohana; Jourdy Cakranegara; Jamari; Budi Setiyana (Fluids)
The aquaculture industry encounters substantial obstacles, including organic pollution, oxygen insufficiency, and elevated levels of ammonia and carbon dioxide. Aeration systems are employed to enhance the process of oxygen transfer and promote circulation. The Lily impeller, a newly developed technology, has demonstrated reduced energy consumption in comparison to conventional impeller designs. The objective of this study is to examine how changes in the cut sweep ratio impact the distribution of dissolved oxygen in shrimp ponds, using computational fluid dynamics (CFD) simulation. A user-defined function (UDF) was utilized to incorporate a dissolved oxygen model into the pond. Five designs of Lily impellers were analyzed and compared with each other. This study demonstrated that alterations in the cut sweep ratio significantly affected the distribution of dissolved oxygen, dynamic pressure, and flow velocity in the pond. The “no cut” variant exhibited the highest average dissolved oxygen value of 0.00385 kg/m3, along with a maximum dynamic pressure of 11.5 Pa and a maximum flow velocity of 0.96 m/s, resulting in the most significant outcomes. This study determined that only the immediate area surrounding the aerator possesses dissolved oxygen levels that are sufficiently elevated to support the survival of shrimp. Consequently, the installation of additional aerators is necessary to guarantee the presence of adequate dissolved oxygen throughout the entire pond.